Komunikasi Organisasi dalam Tata Kelola Desa: Interaksi Multiarah untuk Mendorong Partisipasi Pembangunan - Warat, Ahmad Rifai; Tuanaya, Wahab (Populis: Jurnal Ilmu Sosial dan Ilmu Politik, 2024)
This article explores organizational communication strategies within village governance aimed at enhancing community participation in local development. The study focuses on how village governments establish multidirectional communication interactions to strengthen citizen engagement in the planning and implementation of development programs. Conducted in Kataloka Village, Maluku, this research adopts a qualitative approach, utilizing in-depth interviews, participatory observation, and document analysis. The findings reveal that the success of community participation is closely linked to the effectiveness of organizational communication employed by the village government, particularly in managing the flow of information through vertical (top-down), horizontal (peer-to-peer), and diagonal (cross-structural) communication. Key challenges identified include limited two-way communication channels and low levels of digital literacy among residents. However, efforts to intensify face-to-face dialogue and actively involve citizens in community forums have proven effective in increasing engagement. The novelty of this study lies in its emphasis on the integration of vertical, horizontal, and diagonal communication flows as a strategic mechanism to reinforce participatory democracy at the local level. This article recommends strengthening the communication capacity of village governments and developing inclusive communication channels as a contribution to the advancement of social sciences, particularly in the fields of organizational communication and rural governance.